1997
DOI: 10.1111/j.1708-8305.1997.tb00803.x
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis in Western Irian Jaya

Abstract: Japanese encephalitis (JE) is one of the emerging infectious diseases now widespread in Asia, with recent extension into Torres Strait in northern Australia.1,2 In Indonesia, JE was not considered to be a serious clinical problem,3 although seroprevalence studies showed high prevalence of JE-neutralizing antibody in residents of Java, Kalimantan, Bali, with low prevalence in Sulawesi, Maluka and Irian Jaya.4 Confirmed clinical cases of JE have been rare in Indonesia and mainly have been reported in the west,3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Subsequent studies revealed that JEV had probably reached the Torres Strait by island hopping, probably undetected in mosquito-bird and mosquito-pig cycles, through the eastern Indonesian archipelago to Irian Jaya and Papua New Guinea (PNG) (Mackenzie et al, 2002b). In support of this hypothesis, JEV had been isolated from mosquitoes collected on Lombok (Olson et al, 1985) and Flores (JG Olson, unpublished results) Islands in 1978to 1979and 1981 antibodies to JEV were found in human sera collected between 1989 and 1995 from Western Province in PNG (Johansen et al, 1997); clinical cases of Japanese encephalitis were reported in Irian Jaya (Spicer, 1997) and PNG (J Oakley, S Flew, CA Johansen, RA Hall, D Phillips, JS Mackenzie, unpublished results) in 1997 to 1998; and JEV was isolated from mosquitoes in Western Province, PNG, in 1997(Johansen et al, 2000. JEV activity continued to occur in the Torres Strait in 1996Strait in , 1997Strait in , and 1998, with seroconversions in sentinel pigs, a further human case in 1998 on Badu, and, for the first time, in Cape York on the Australian mainland (Hanna et al, 1999), but no activity was detected in 1999.…”
mentioning
confidence: 95%
“…Subsequent studies revealed that JEV had probably reached the Torres Strait by island hopping, probably undetected in mosquito-bird and mosquito-pig cycles, through the eastern Indonesian archipelago to Irian Jaya and Papua New Guinea (PNG) (Mackenzie et al, 2002b). In support of this hypothesis, JEV had been isolated from mosquitoes collected on Lombok (Olson et al, 1985) and Flores (JG Olson, unpublished results) Islands in 1978to 1979and 1981 antibodies to JEV were found in human sera collected between 1989 and 1995 from Western Province in PNG (Johansen et al, 1997); clinical cases of Japanese encephalitis were reported in Irian Jaya (Spicer, 1997) and PNG (J Oakley, S Flew, CA Johansen, RA Hall, D Phillips, JS Mackenzie, unpublished results) in 1997 to 1998; and JEV was isolated from mosquitoes in Western Province, PNG, in 1997(Johansen et al, 2000. JEV activity continued to occur in the Torres Strait in 1996Strait in , 1997Strait in , and 1998, with seroconversions in sentinel pigs, a further human case in 1998 on Badu, and, for the first time, in Cape York on the Australian mainland (Hanna et al, 1999), but no activity was detected in 1999.…”
mentioning
confidence: 95%
“…Serologic evidence also suggests that JE virus has spread from the Western Province into the Southern Highlands and Gulf Provinces (17) and that it has emerged in the West Sepik Province in the north and been responsible for outbreaks of encephalitis on Normanby Island and at Alatau in Milne Bay Province in the eastern part of the country. A probable human case of JE infection has also been reported from Irian Jaya (20), and antibodies to JE have been found in human serosurveys there (21). The rapidity with which JE virus has spread through Papua New Guinea places some nearby Pacific nations, such as the Solomon Islands and Vanuatu, at risk.…”
mentioning
confidence: 99%
“…Mackenzie, unpublished results). A case of encephalitis due to JE virus infection was also reported from the Timika area of Irian Jaya in 1997 (SPICER 1997), and subsequent serological studies demonstrated that several indigenous persons had antibodies to the virus (SPICER et al 1999).…”
Section: Je Virus In Papua New Guinea and Irian Jayamentioning
confidence: 91%